PEMANFAATAN TEPUNG AMPAS TAHU PADA PEMBUATAN KUKIS MENGANDUNG MINYAK SAWIT MERAH - Apriadi Kaahoao; Netti Herawati; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to get the best formulation of substitution of wheat flour with okaraflour in making of cookies containing red palm oil, judging from the content of nutrients and organoleptic tests based on SNI 01-2973-1992. The research was conducted with an experimental method using a completely randomized design with four treatments and four replications. The treatment in this study were ratio of wheat flour and okara flour 100%:0%, 75%:25%, 50%:50%, and 25%:75%. Data were statistically analyzed by using Analysis of Variance and followed by Duncan's New Multiple Range Test at level5%.Results of the analysis showed that ratio of wheat flourand okara flour significantlyaffected on moisture, ash, protein,and crude fiber content as well as descriptive and hedonic sensory test of the cookies. Based on this research, the best treatment wasratio of wheat flourand okara flour 75%:25% which hadmoisture 2.37%, ash 1.62%, protein 6.21%,and crude fiber content 3.80%.Characteristics cookies of best treatment based on descriptive test was  golden yellow color, rather beany flavor, rathertofu tasteless, and crunchy texture. Keywords: Cookies, okara flour, wheat flour, red palm oil.